Intensitas Dan Prevalensi Ektoparasit Pada Kepiting Bakau (Scylla serrata) Pada Perairan Payau Desa Cadek Kecamatan Baitussalam Aceh Besar - Danesti, Yelga; Dewiyanti, Irma; Arisa, Iko Imelda (Universitas Gajah Putih, 2022)
Research has been carried out on the intensity and prevalence of ectoparasites in mud crabs (Scylla serrata) in the brackish waters of Cadek Village, Baitussalam District, Aceh Besar in November to December 2020. The purpose of this study was to determine the types of types of ectoparasites, prevalence and intensity found in mud crab (Scylla serrata) in Cadek Village, Baitussalam District, Aceh Besar District. Sampling conducted randomly and the data were analyzed descriptively in the form of tables and figures. The results showed that the types of ectoparasites that infect crabs mangroves in the brackish waters of Cadek Village, namely Octolasmis and Zoothamnium sp. Value prevalence of ectoparasites infesting Scylla serrata in the brackish waters of Cadek. Village is Zoothamnium sp. 40% and Octolasmis sp. 90% are included in the category of parasites it almost always infests Scylla serrata. The intensity value of the type of ectoparasites Infesting Scylla serrata in the brackish waters of Cadek Village is Zoothamnium sp. 6.75 parasite/tail and Octolasmis sp. 69 parasites/tails that fall into the category of infestation very heavy.